Gender and Migration IMISCOE Short Reader - Christou, Anastasia (IMISCOE Research Series, 2022)
This open access short reader offers a critical review of the debates on the transformation of migration and gendered mobilities primarily in Europe, though also engaging in wider theoretical insights. Building on empirical case studies and grounded in an analytical framework that incorporates both men and women, masculinities, sexualities and wider intersectional insights, this reader provides an accessible overview of conceptual developments and methodological shifts and their implications for a gendered understanding of migration in the past 30 years. It explores different and emerging approaches in major areas, such as: gendered labour markets across diverse sectors beyond domestic and care work to include skilled sectors of social reproduction; the significance of families in migration and transnational families; displacement, asylum and refugees and the incorporation of gender and sexuality in asylum determination; academic critiques and gendered discourses concerning integration often with the focus on Muslim women. The reader concludes with considerations of the potential impact of three notable developments on gendered migrations and mobilities: Black Lives Matter, Brexit and COVID-19. As such, it is a valuable resource for students, academics, policy makers, and practitioners.